Analysis of community behavior on garbage disposing in Batang Bakarek-Karek river basin of Padang Panjang - Novriza Yulida; Agus Suwarni; Sarto Sarto (Berita Kedokteran Masyarakat (BKM), 2016)
Community behavior in garbage disposal in Batang Bakarek-Karek river basin of Padang PanjangPurposeThe purpose of this study was to analyze the behavior of the people who live around Batang Bakarek-Karek river in disposing of their garbage, which included, knowledge, attitudes, infrastructure, and implementation of government policies of Padang Panjang West Sumatra.MethodsThis research used a cross-sectional survey design. Subjects were breadwinners of the families who live in the watershed of Batang Bakarek-Karek river including 118 people. The independent variables in this study were knowledge, attitude, infrastructures and policy implementation. The dependent variable was waste behavior. Data analysis was performed by using univariate, bivariate analysis with chi-square tests, followed by multivariate analysis using logistic regression tests.ResultsStatistical analysis determined that all the studied variables were significantly related to people's behavior in disposing of their waste, including knowledge, attitude, infrastructure, and policy implementation. The most influential variable on people's behavior in disposing of their waste was their attitude with the value of OR as 7.79. ConclusionAttitude was the most influential variable on people’s behavior in Batang Bakarek-Karek river in disposing of their waste. This research suggests the need for guidance and socialization of waste management policy.